Crossing confessional boundaries exemplary lives in Jewish, Christian, and Islamic traditions - Renard, John, 1944- (S. Mark Taper Foundation imprint in Jewish studies., 2020)
"Arguably the single most important element in Abrahamic cross-confessional relations has been an ongoing mutual interest in perennial spiritual and ethical exemplars of one another's communities. Ranging from Late Antiquity through the Middle Ages, Crossing Confessional Boundaries explores the complex roles played by saints, sages, and Friends of God in the communal and intercommunal lives of Christians, Muslims, and Jews across the Mediterranean world, from Spain and North Africa to the Middle East to the Balkans. By examining these stories in their broad institutional, social, and cultural contexts, Crossing Confessional Boundaries reveals unique theological insights into the interlocking histories of the Abrahamic faiths"--